Special issue on interaction with coupled and public displays - Quigley, Aaron; Subramanian, Sriram; Izadi, Shahram (Personal and Ubiquitous Computing, 2009)
Recent developments have seen the widespread proliferation of both large public displays and small personal display technologies. In parallel, novel forms of human–computer interaction such as multi-touch technology have transformed these devices from passive displays into interactive systems. Examples of such small displays include PDAs, Tablets and iPhones while examples of large interactive surfaces (multi-touch driven displays) include the Diamondtouch and Microsoft Surface. With these, users can now interact directly with the displayed objects by simply touching the display, creating a sense of immediacy and natural interaction. This sense of immediacy gives rise to a range of human–computer interactions along with support for multi-device or public display collaborative activities.